Virtual Symposium Designed as an Innovative Approach to Disseminate Leadership Development Content - Kerry K Fierke; Whitney D Maxwell; Gregory M Zumach (University of Minnesota Libraries Publishing, 2021)
The American Association of Colleges of Pharmacy (AACP) Leadership Development Special Interest Group (LD SIG) embarked upon a one-week virtual symposium (VS) across three years. The purpose of the VS was to disseminate leadership content, case studies, and various topics of interest utilizing technology. This electronic format provided a new communication approach to facilitate content and discussion of leadership materials amongst faculty colleagues nationally. The VS allowed participants to gain knowledge and skills to address leadership development in a timely, flexible manner that can be challenging during in-person professional meetings and conferences due to conflicting programming and travel limitations. Evaluators across each of the VS (100%) indicated that they either agreed or strongly agreed with the scaled evaluative statements that the video presentations met their educational needs.